Distributions of gas hydrate and free gas accumulations associated with upward fluid flow in the Sanriku-Oki forearc basin, northeast Japan. (June 2020) - Kret, Kakda; Tsuji, Takeshi; Chhun, Chanmaly; Takano, Osamu
Abstract: We applied automated velocity analysis to a 3D seismic data volume to obtain a high-resolution seismic velocity model that we used to investigate the influence of fluid behavior on the subsurface distribution of gas in the Sanriku-Oki forearc basin, northeast Japan. We identified free gas accumulations as zones of low P-wave velocity separated from overlying high-velocity gas hydrates by the clear seismic boundary of the bottom-simulating reflection (BSR) between them. We then used conductive modeling to map upward heat flow in our study area from the depth of the BSR derived from the velocity model. The estimated heat flow demonstrates that upward fluid flux has considerable influences on the distributions of both gas hydrate and free gas. The areas of high heat flow (representing high fluid flux) correspond to underlying permeable geological features such as gas chimneys, faults, and the edges of porous slumps, suggesting that these features provide fluid migration pathways from Eocene to Oligocene source rocks to free gas and hydrate accumulations in overlying sedimentary rocks. The techniques we have employed can contribute to the high-resolution mapping of gas hydrate and free gas accumulations in similar deep-water reservoirs off the eastern continental margin of Japan and at tectonically similar plate subduction margins in other regions. Highlights: High-resolution velocity model by applying automatic analysis to 3D seismic data. Reveal accumulation of hydrate and free-gas from the high-resolution velocity model. Map heat flow in our survey area using the depth of bottom simulating reflection. High heat flow areas agree with locations of the highly-accumulated hydrate and gas. The areas of high heat flow correspond to underlying permeable geological features.